Physical activity levels during COVID-19 pandemic and its associated factors in patients with Chagas disease - Xavier, Isis Gabrielli Gomes; Andrade, Patrícia Mello; Vitor, Rodrigo de Lima; Barros, Tayná Cruz; Portela, Luciana Fernandes; de Holanda, Marcelo Teixeira; Sangenis, Luiz Henrique Conde; Sperandio da Silva, Gilberto Marcelo; Mazzoli-Rocha, Flavia; Mendes, Fernanda de Souza Nogueira Sardinha; da Costa, Andréa Rodrigues; Quintana, Marcel de Souza Borges; et al. (Frontiers in Medicine, 2024)
Background A better understanding of the consequences of the Coronavirus Disease 2019 (COVID-19) pandemic on lifestyle of patients with Chagas disease (ChD) is of paramount importance to facilitate the implementation of intervention strategies tailored to this specific population. Objective The present study aimed to evaluate the level of physical activity (PA) in Chagas disease (ChD) patients during the Coronavirus Disease 2019 (COVID-19) pandemic and its main associated factors. Methods This is a cross-sectional study with 187 patients of both sexes, aged ≥18 years, followed in a national infectious disease center (Rio de Janeiro, Brazil). The level of PA was determined by the International Physical Activity Questionnaire short version and expressed in terms of total volume of physical activity (PA) (MET-minutes per week). Individuals were classified as physically active following the 2020 World Health Organization PA guideline. The exposure variables were age, sex, race, marital status, schooling, income per capita, number of rooms per domicile, number of residents per domicile, body mass index, clinical form of ChD, COVID-19 antibodies, comorbidities, self-reported anxiety, self-reported depression, self-reported fear, and self-reported sadness. The association between the exposure variables with total PA (as a continuous variable) was determined using univariate and multivariate linear regression models. Results Mean age was 61.1 ± 11.6 years. Most (62%) were women and self-declared their race as mixed (50.8%). The percentage of physically active individuals according to was 52%. The variables independently associated with total PA levels were non-white race (Exp β = 1.39; 95% CI 1.02 to 1.90), dyslipidemia (Exp β = 0.73; 95% CI 0.56 to 0.95) and self-reported depression during quarantine (Exp β = 0.71; 95% CI 0.52 to 0.96). Conclusion Non-white race was positively associated with total levels of PA, while dyslipidemia, and self-reported depression during quarantine were negatively associated with total levels of PA. The identification of associated factors can facilitate the development of tailored strategies to increase PA levels ChD patients.